Persepsi Guru Pendidikan Agama Kristen Terhadap Amanat Agung Yesus Kristus Sebagai Dasar Etika Profesi Pendidik - Elfin Warnius Waruwu (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2023)
This study aims to analyze the perceptions of Christian Religious Education teachers towards the Great Commission of Jesus Christ as the basis for the ethics of the teaching profession. The Great Commission of Jesus Christ contains important moral values in the educational context, such as love, justice, humility, forgiveness, and social responsibility. This study uses the library method. In the library method, the writer will search and select information sources that are relevant to the research topic. The results of this research can contribute to the development of an educational approach that focuses on spiritual and ethical values, as well as provide a better understanding of the challenges faced by teachers in integrating religious values into a diverse school environment.